1989
DOI: 10.1111/j.1399-302x.1989.tb00402.x
|View full text |Cite
|
Sign up to set email alerts
|

Immunomodulatory effects of Bacteroides products on in vitro human lymphocyte functions

Abstract: Bacteroides spp. have been implicated in the pathogenesis of several diseases, including periodontal diseases. In this study sonic extracts of 6 Bacteroides spp. were examined for their abilities to alter human lymphocyte function. We found that soluble extracts from Bacteroides intermedius, Bacteroides endodontalis, Bacteroides asaccharolyticus, Bacteroides melaninogenicus, and to a lesser degree Bacteroides loescheii, caused dose-dependent inhibition of human lymphocyte responsiveness to both mitogens and an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
14
0

Year Published

1992
1992
2012
2012

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(16 citation statements)
references
References 20 publications
2
14
0
Order By: Relevance
“…Other studies also demonstrated lymphocyte suppression by periodontopathic bacteria. Low responses to P. gingivalis , Treponema denticola, and Capnocytophaga ochracea were found in both healthy and periodontitis peripheral blood lymphocytes compared with other oral bacteria (Stashenko et al ., 1983), and in another study, P. gingivalisreduced the response of non-mitogen-stimulated cells (Shenker and Slots, 1989;. A. actinomycetemcomitans was also shown to suppress the peripheral blood lymphocyte response to mitogens (Shenker et al ., 1982a), and depletion of CD8 cells was found to abrogate this response, suggesting the induction of a CD8 suppressor factor (Shenker et al ., 1982b).…”
Section: (Iv) Adaptive Immunitymentioning
confidence: 99%
“…Other studies also demonstrated lymphocyte suppression by periodontopathic bacteria. Low responses to P. gingivalis , Treponema denticola, and Capnocytophaga ochracea were found in both healthy and periodontitis peripheral blood lymphocytes compared with other oral bacteria (Stashenko et al ., 1983), and in another study, P. gingivalisreduced the response of non-mitogen-stimulated cells (Shenker and Slots, 1989;. A. actinomycetemcomitans was also shown to suppress the peripheral blood lymphocyte response to mitogens (Shenker et al ., 1982a), and depletion of CD8 cells was found to abrogate this response, suggesting the induction of a CD8 suppressor factor (Shenker et al ., 1982b).…”
Section: (Iv) Adaptive Immunitymentioning
confidence: 99%
“…Various studies have assessed the pathogenic potential of P. gingivalis and A. actinomycetemcomitans (26,39,45). P. gingivalis has been shown to produce potentially cytotoxic molecules that enhance lymphoproliferative responses and immunoglobulin production in vitro (32). Furthermore, the lipopolysaccharide from P. gingivalis has been shown to stimulate cytokine production, such as interleukin-ip and' tumor necrosis factor, by macrophages (22,30).…”
mentioning
confidence: 99%
“…In rat pulpitis experimentally induced by specific bacteria, Streptococcus mutans, Porphylomonas endodontalis stimulated the production of Interferon-γ , IL-2 and IL-4 14) . These studies showed that P. endodontalis have inflammatory effects by stimulation, but in other reports, sonic extract of P. endodontalis in lymphocyte in vitro have immunosuppressive effects by inhibition 19) , and in this study E. faecalis inhibited the cytokine production of lymphocytes. Much further investigation is required to clarify the stimulation and inhibition of cytokines.…”
Section: ⅳ Discussionmentioning
confidence: 69%
“…Sonicated extract from Prevotella intermedia, Porphylomonas asaccharolytica, Porphyromonas endodontalis and Prevotella melaninogenica were capable of suppressing human T-and B-cell response in dose-dependent manner. The immunosuppressive activity is nondialyzable and heat labile 19) . This study showed that the level of IL-2 and IL-4 in lymphocytes stimulated with PHA were significantly higher than those of the negative control group.…”
Section: ⅳ Discussionmentioning
confidence: 99%